Analysis of the marketing channels of Coffee - Fery Murtiningrum; Gracia Gabrienda (Journal of Agri Socio Economics and Business, 2019)
In Bengkulu Province, the area of coffee plantations reached 124,510 hectares spread in several districts with production reaching 60,790.08 tons per year (BPS, 2018). Most coffee production (Coffea Spp) is produced by smallholder farmers. Nearly a quarter of the coffee production was produced by Rejang Lebong Regency, namely: 13,459 tons with a total plantation area of 27,828.12 hectares of coffee plantations. Constraints in the development of coffee are in the case of coffee marketing channels that have not been maximized by farmers, transportation due to the topography of the area and the location of the factory that is far away, low marketing production, quality of coffee (quality ), and capital that influences the selling price of the coffee. This situation is certainly inseparable from the influence of the factors of the coffee industry production itself, namely in the form of capital, raw materials, labor, transportation, marketing and income of business owners that also affect the income of workers. For this reason, researchers are interested in researching the marketing channels of Coffee in Rejang Regency. Lebong, and analyze the efficiency of the Coffee marketing channel in Rejang Lebong Regency. From the results of the study, it was found that the coffee marketing channel occurred in Rejang Lebong Regency had 5 types of marketing channels. Marketing margins and the biggest profits are obtained by large traders.